Stochastic Two Species Model with Prey Refuge: an Application to Keoladeo National Park, India - Kant, Shashi (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we investigate a stochastic two species prey-predator system with prey refuge. The contribution of this paper is (a) To Propose a Lotka-Volterra stochastic model with prey refuge (b) Singular cases are very interesting and it is found that without the prey population, the predators died with probability one while without predator population prey population fallen between 0 & ∞. Impact of refuge term is also observed. (c) The Radon-Nikodym Derivative is derived for the proposed model (d) Asymptomatic analysis and moment estimation for the proposed model is also carried out. As a possible application of proposed stochastic model, Keoladeo National Park, India is considered.